The Artist’s Resale Right: Global Perspectives and Vietnam’s Path to Protection under the EVFTA - Tuan, Tran Anh; Kien, Tran (Hasanuddin Law Review, 2025)
The artist’s resale right, enabling visual artists to receive royalties from secondary market sales, is a pivotal intellectual property mechanism with varied global adoption. This article traces its historical evolution from early 20th-century legislation to its inclusion in international frameworks, contrasting the European Union and United Kingdom’s harmonized approaches with the United States’ rejection due to differing copyright philosophies. It examines the resale right provisions in a new-generation free trade agreement, analyzing Vietnam’s current legal gap under its intellectual property framework and the feasibility of incorporation. The article evaluates arguments for and against the resale right, highlighting its role in promoting artist equity and creative incentives against concerns of market distortion and administrative burdens. It argues that Vietnam should adopt the resale right to align with global standards, proposing solutions to legal, cultural, economic, and political challenges. This analysis offers insights for jurisdictions navigating intellectual property integration in trade agreements.